Pentingnya Badan Klasifikasi Kapal Dalam Industri Maritim - Santhi Wilastari (Politeknik Ilmu Pelayaran Semarang, 2020)
Ship Classification Agency is a service business that is different from other industrial fields. By looking at the links and participation in the pace of the maritime industry and the existence of the Ship Classification rules which were made as a reference, the essence of the existence of shipping services from the Classification Board has a strong background to support the advancement of the maritime industry. Clearly, the Ship Classification Bureau must establish and establish standards or benchmarks, guidelines or rules for reference from planning, construction, and periodic surveys of commercial ships and other forms of marine building construction. Class certificate which shows the regulations of the rules will describe the ship concerned as having the construction feasibility and the machines to be used as planned. Thus, a ship classified will provide security for life and the goods transported on the ship, including the prevention of pollution from the surrounding sea which is caused in its operations.